Kajian Perilaku Harimau Sumatera (Panthera Tigris Sumatrae) - Arum Zaharani; Melati Latifah; Rina Zaryanti; Suci Fajrina; Abdul Razak (LPPM Universitas Cipta Mandiri, 2024)
The Sumatran tiger (Panthera tigris sumatrae) is one of the largest predators whose distribution covers almost all of mainland Asia to several islands in Indonesia. The study of the behavior of the Sumatran tiger (Panthera tigris sumatrae) regarding the typical behavior of individual tigers is very important to provide insight and knowledge about the behavior of the Sumatran tiger (Panthera tigris sumatrae). In this article, the author collects information about Sumatran tiger behavior based on daily behavior such as resting, socializing, moving, grooming, drinking, eating, defecating, and other activities. The method used is the literature study method. This review provides information showing that the highest resting activity of Sumatran tigers during the day is due to the hot daytime temperatures causing tigers to prefer to sleep and laze around. It is also known that grooming and bathing activities are the activities with the highest percentage of duration, and male tigers do more moving activities than female tigers. Researchers hope that this review can provide knowledge and insight into the behavior of the Sumatran tiger (Panthera tigris sumatrae).